Frequency of Hakeem Prescribed Medicinal Intake in Patients Presenting with Pancytopenia in a Tertiary Care Hospital - Saria Munir, Muneeza Natiq, Rabia Azmi, Maria Qaiser (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pancytopenia is a common disorder faced by physicians, especially haematologists, in their daily clinical practice. Hakeem prescribed medications have been implicated as causative agent for inducing pancytopenia but frequency of such cases has not yet been reported. This study was conducted to assess the frequency of Hakeem medication in patients presenting with pancytopenia in a tertiary care hospital Patients and methods: This prospective cross-sectional study was conducted at the Department of Haematology, Allama Iqbal Medical College / Jinnah hospital, Lahore from October 2021 to February 2022. 135 patients referred to the Department of Haematology for investigation of pancytopenia were enrolled into the study through non-probability consecutive sampling after they fulfilled the selection criteria. They were inquired about taking medicines given by hakeem prior to their index visit to the hospital. Demographics and history were recorded on a specially designed proforma. Data was analyzed using SPSS version 20. Results: 135 referred patients presenting with pancytopenia were enrolled into the study. Mean age of the sample population was 33.14 ± 15.57 years. There were 92 (68.1%) males and 43 (31.9%) females. For their current medical condition, 40 (29.63%) patients were using Hakeem prescribed medicines with or without concomitant use of allopathic medicines, whereas 79 had no prior treatment at all. Conclusion: The use of Hakeem prescribed medications is high in our sample population and cannot be ignored as a causative agent for occurrence of pancytopenia. Keywords: Pancytopenia, Anaemia, Hakeem medication, Platelet count, Total leucocyte count, Absolute neutrophil count